Independent Non-Executive Directors, Managerial Ownership And Firm Performance In Malaysian Public Listed Companies - Kanapathy, K. Vethanayagam (2005)

(untitled)
Leung and Horwitz (2004) argued that the failing of corporate governance and lack of transparency are often associated with the Asian financial crisis.